Analisis Kehandalan Sistem Tenaga Listrik di PT. PLN (Persero) Rayon Fakfak dengan Metode Loss of Load Probability: Analysis of Electrical Power System Reliability at PT. PLN (Persero) Rayon Fakfak Using the Loss of Load Probability Method - Zulfikar Bungin; Adelhard Beni Rehiara; Yanty Rumengan (JISTECH: Journal of Information Science and Technology, 2022)
The level of reliability determines the continuity of electricity distribution in the power system, the availability of insufficient power will affect the level of reliability of the system. The Loss of Load Probability (LOLP) method is a popular method to calculate the reliability of an electric power system. A high level of reliability is obtained with a small level of risk. The value of the disturbance in the generating units, or the forced outage rate (FOR), is calculated using the installed power data and the disturbance data of each unit. The probability of each generating unit, the probability when another generating unit is added, and the cumulative probability can be calculated based on the FOR value. From the intersection point of the interval of the load curve in one year, the intersection is reached on the 346th day with 720 kW, which is the force outage limit. The results of the LOLP calculations show that the electric power system at PT. PLN Rayon (Persero) Fakfak has experienced a forced outage for about 90.5828 days per year.